Answer:
Step-by-step explanation:
let sum of zeros=s
and product of zeros=p
then quadratic equation is x²-sx+p=0
x²-(-1/2)x+(-3)=0
x²+1/2 x-3=0
2x²+x-6=0
Answer:
5/6
5/6 Is the simplified answer the unsimplified answer is 15/18
The equation be 50x = 17 then the value of x = 17/50.
<h3>How to find the value of x?</h3>
To estimate the value of x, bring the variable to the left side and bring all the remaining values to the right side. Simplify the values to estimate the result.
Let the equation be 50x = 17
Diving both sides of the equation by 50, we get
50x/50 = 17/50
x = 17/50
Therefore, the value of x = 17/50.
To learn more about the expression refer to:
brainly.com/question/723406
#SPJ4
You want to figure out what the variables equal to, all of these are parallelograms meaning opposite sides and angles are equal to each other.
In question 1 start with 3x+10=43, this means that 3x is 10 less than 43 which is 33, 33 divided by 3 is 11 meaning x=11.
Same thing can be done with the sides 124=4(4y-1), start by getting rid of the parentheses with multiplication to get 124=16y-4, this means that 16y is 4 more than 124, so how many times does 16 go into 128? 8 times, so x=11 and y=8
Question 2 can be solved because opposite angles are the same in a parallelogram, so u=66 degrees
You can find the sum of the interial angles with the formula 180(n-2) where n is the number of sides the shape has, a 4 sided shape has a sum of 360 degrees, so if we already have 2 angles that add up to a total of 132 degrees and there are only 2 angles left and both of those 2 angles have to be the same value then it’s as simple as dividing the remainder in half, 360-132=228 so the other 2 angles would each be 114, 114 divided into 3 parts is 38 so u=66 and v=38
Question 3 and 4 can be solved using the same rules used in question 1 and 2, just set the opposite sides equal to each other
D.
![3 y^{3}x+9 x^{2} y-2 y^{2} -4x](https://tex.z-dn.net/?f=3%20y%5E%7B3%7Dx%2B9%20x%5E%7B2%7D%20y-2%20y%5E%7B2%7D%20-4x)
Take each term and find the degree of the term and then put them in order from highest to lowest:
![y^{3}x=3+1=4](https://tex.z-dn.net/?f=%20y%5E%7B3%7Dx%3D3%2B1%3D4%20)
![x^{2} y=2+1=3](https://tex.z-dn.net/?f=%20x%5E%7B2%7D%20y%3D2%2B1%3D3)
![y^{2}=2](https://tex.z-dn.net/?f=%20y%5E%7B2%7D%3D2%20)
x=1
Remember a letter without an exponent is assumed to be a 1.
Hope that helps.